Effects of Different Oils on Absorption of Caffeic and Vanillic Acids in Wistar Rats - Prasadani, W.C.; Seneviratne, K.N.; Ekanayake, S. (Proceedings of 2nd Scientific Sessions Sri Lanka Association for Laboratory Animai Science (SLALAS) January 16th & 17th 2015, 2015)
Attached

B a ck g ro u n d The am ount of antioxidants absorbed from a m eal w ill depend on b ioavailability irrespective o f the quantity found in a m eal,. D ietary fatty-acids are reported to increase absorption o f calcium and drugs by regulating the tigh t junction perm eability. Objective Compare the effect of soybean o il (SO), coconut o il (CO) and olive o il ( 0 0 ) on the absorption of two phenolic antioxidants, caffeic (CA) and van illic (VA) acids. Method M ale W istar rats (5 w eeks, 180-200g) w ere random ly divided into six groups [(n=7), (eth ical approval 13/14)]. Three d iets w ere prepared u sin g the three o ils and for each oil, two groups w ere m aintained. One group o f each o il w as fed a d iet including CA and VA and the other group excluding them . Faeces w ere collected on day 0 and 19th,20th and ^Lstdays, extracted, purified and injected to HPLC. Results On day 0, CA and VA could not be found in the faeces of rats fed different oils w ith and w ith ou t CA and VA. The VA in faeces w as not detected after 20 days in all the groups. However, CA w as detected in the faeces o f rats fed w ith different oils. The order of excretion of CA in faeces o f rats is SO< C 0 < 0 0 . A significant difference (p < 0.05) in excretion w as observed betw een SO and OO and CO and 0 0 . T here w as no sign ifican t difference (p>0.05) in the excretion of CA betw een SO and CO. C o n clu sio n It can be concluded that the absorption of CA is facilitated by SO and CO m ore than 0 0 .
Keywords: Caffeic acid; coconut oil; intestinal absorption; vanillic acid; Wistar rats